The Use of Science Media Learning in Grade 7 in SMPIT Al-Yasmin Bogor - Ghaida Sekarlita Fadha Supriadi; Diana Rochintaniawati (Yayasan Darussalam Bengkulu, 2021)
This study aims to determine the use of instructional media in science learning. The subjects of this study were students of grade 7 SMP. The data collection technique used was non-participant, with the sampling technique used was purposive sampling. The results showed that the percentage of student responses from SMPIT Al-Yasmin Bogor to learning media with an indicator of the use of learning media was 83.67% on average, on the indicators of students' attitudes towards using media an average of 70.80%, on the indicator of the frequency of using learning media obtained average response is 70.83% and indicators of benefits in using learning media get an average percentage of 68.86%. Through this research, it was revealed that the use of science learning media in grade 7 SMPIT Al-Yasmin Bogor was good and varied.